IMPLEMENTING THE TALKING CHIPS LEARNING MODEL TO IMPROVE STUDENT ACHIEVEMENT IN CULTURAL ARTS (ART THEORY) - Thahrim, Muhammad Zul; Syahrir, Nurlina; B, sukarman (Universitas Negeri Makassar, 2025)
The purpose of this study was to examine: (1) teacher activity, (2) student activity, (3) student responses, and (4) student learning outcomes following the implementation of the Talking Chips learning model in art appreciation (visual arts) instruction. This research employed a classroom action research design. Data were collected through classroom observations, interviews, questionnaires, and multiple-choice achievement tests. The results demonstrated notable improvements across two instructional cycles. Teacher activity increased from 70% in Cycle I to 93% in Cycle II. Student activity likewise improved from 81% to 89%. Student responses toward the Talking Chips model were predominantly positive, with 93.60% categorized as good and only 6.38% categorized as low. Furthermore, the average student achievement score increased substantially from 58.66% in Cycle I to 79.75% in Cycle II. These findings indicate that the Talking Chips learning model in art appreciation effectively enhances both student motivation and learning outcomes among Grade XI Science students at MA DDI Kanang.